COACHING STRATEGIES FOR CORPORATE INNOVATION : a systemic approach to coaching teams and leaders. - YONG, IVAN (ROUTLEDGE, 2025)
Drawing upon the authors' own extensive experiences within the field, and melding startup dynamics with corporate innovation, the book equips readers to navigate the complexities of this emerging innovation practice.Collaboration between large corporations and innovative startups represents a strategic pillar of corporate innovation and is growing at a rapid pace globally. Such engagements are situated within the broader paradigm of open innovation and are categorised explicitly as corporate venturing when they involve mechanisms such as strategic investments, partnerships, incubators, or co-development initiatives. Leveraging the authors' extensive experience in startup investment, mentorship, and corporate innovation thought leadership forums, this book addresses the critical need for innovation coaching strategies to succeed in this dynamic corporate-startup collaboration. Through a synergy of practical insights, riveting case studies, and authoritative thought leadership, readers will be guided on a transformative journey encompassing innovation culture, symbiotic partnerships with startups, and the coaching strategies pivotal for unlocking innovation advantage.This book is tailored for corporate leaders, innovation teams, corporate venture capitalists, and professional coaches aspiring to transcend conventional wisdom in the current corporate innovation practices.
Keywords: Executive coaching.; Organizational change.; elektronické knihy; electronic books